1990
DOI: 10.1103/physreva.42.6526
|View full text |Cite
|
Sign up to set email alerts
|

Dielectronic capture processes in highly charged uranium ions

Abstract: Dielectronic capture processes in highly charged uranium ions are studied in the isolatedresonance, distorted-wave approximation.A fully relativistic Dirac-Fock method is employed to calculate resonant transfer and excitation cross sections for collisions of U + and U' + with H2 and dielectronic recombination cross sections associated with the 2p~2s stabilizing transition of U' +.A semirelativistic method based on the previously developed AUTOSTRUCTURE code is found to give cross sections in good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…The code can make use both of nonrelativistic and semi-relativistic wavefunctions (Pindzola & Badnell 1990). The low-n problem is no different from the one of computing atomic structure.…”
Section: Dielectronic Recombination Rate Coefficient Modellingmentioning
confidence: 99%
“…The code can make use both of nonrelativistic and semi-relativistic wavefunctions (Pindzola & Badnell 1990). The low-n problem is no different from the one of computing atomic structure.…”
Section: Dielectronic Recombination Rate Coefficient Modellingmentioning
confidence: 99%
“…While the semirelativistic approach of AUTOSTRUCTURE cannot hope to give energy splittings to high precision in such highly relativistic systems (and so makes use of the best available N-electron energies instead [6]), its description of radiative and autoionization rates has been shown to be accurate, at least for l =0-5 [1]. There being no obvious reason why the semirelativistic approach should fail for high l, we have reexamined the problem.…”
mentioning
confidence: 94%
“…Multiconfiguration Dirac-Fock (MCDF) calculations were carried out for the 2p 3/2 6l resonances, and for l =0-5 of the 2p 1/2 nl resonances (for n ജ 20). The contribution from higher l for the 2p 1/2 nl resonances was determined using the multiconfiguration BreitPauli (MCBP) semirelativistic approach incorporated within the AUTOSTRUCTURE code [6], which includes the massvelocity and Darwin terms within the solution of the radial equations. Subsequently, measurements were made at GSI [2] for DR via the 2p 1/2 20l resonances and these were found to be in good agreement with MCDF calculations [2], which were made for all l. Good agreement was found also with the MCDF results of Mitnik et al [4], but the semirelativistic results reported by them were found to be a factor of 3 smaller than the measurements and MCDF results of Brandau et al [2].…”
mentioning
confidence: 99%
“…The  code (Badnell 1986;Badnell & Pindzola 1989;Badnell 1997) is used to calculate multiconfiguration intermediate coupling energy levels, radiative rates and autoionization rates. The code can make use both of non-relativistic and semi-relativistic wavefunctions (Pindzola & Badnell 1990). The calculations have been produced in intermediate coupling (IC) approximation.…”
Section: Theorymentioning
confidence: 99%
“…Prior to the final DR calculations, the ionic thresholds were shifted to the known spectroscopic values (http://physics.nist.gov/cgi-bin/ AtData/main_asd) by a small amount -typically in the range of 1-2 eV for high Z. The calculations for Ti 15+ , and beyond, were performed in the semirelativistic approximation for the radial wave functions, developed by Cowan & Griffin (1976) and implemented in  as is explained in Pindzola & Badnell (1990). Non-relativistic radial functions were used otherwise.…”
Section: Theorymentioning
confidence: 99%